Efektivitas Penambahan Aditif Pasir Silika pada Paraffin Wax untuk Media Penyimpan Panas Water Heater - Putu Riska Resita Dewi; Diana Alia; Dirhamsyah Dirhamsyah; Henna Nurdiansari; Femmy Asdiana (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This research develops an automated temperature control system for water heaters, that is both efficient and stable, driven by the need for energy-saving heating solutions, particularly for marine applications. The main objective was to create an automatic system capable of maintaining water temperature within an optimal range while maximizing energy efficiency through the use of thermal storage materials. The methodology involved an on-off control system based on a microcontroller as the main controller, capable of processing temperature sensor data in real time. This system intelligently activates and deactivates the heater to keep the water temperature stable. Paraffin wax was used as a latent heat storage medium, playing a crucial role in gradually storing and releasing thermal energy to support temperature stability. An automatic water heater system based on the ESP32 microcontroller with an on-off control mechanism was successfully designed using paraffin wax combined with silica sand as a thermal storage medium. The addition of silica sand significantly enhanced heat conductivity and temperature stability. Test results showed a substantial reduction in energy consumption, with daily savings reaching Rp12,762.88, equivalent to 67% of total daily energy costs. Over a one-year period, the total savings amounted to Rp4,658,103.20, demonstrating that the paraffin wax–silica sand combination is highly effective in improving energy efficiency and reducing long-term operational costs.